Designing an Intuitive Android Based m-Learning to Support Students in Learning Fundamental Java Programming - Brata, Komang Candra; Ahmad Afif Supianto; Fadhyl Farhan Alghifari (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
In the context of a Computer Science Major in Indonesian higher education, Java programming language is not only one of the most essential programming languages courses but is also considered to be challenging to learn. This fact has led to the development of numerous mobile learning (m-learning) applications to assist learners in acquiring Java programming skills independently. Most existing Java learning assistants are presented on websites or computer platforms which can only be accessed when students open their computer or Laptop and it mostly focuses on enhancing coding abilities, and practical hands-on. While these aspects are crucial, understanding the programming concepts and guided practice are equally essential in fundamental Java programming learning. This paper presents the concept of practical coding exercises in an m-learning application, providing a new interactive approach for learners as an alternative tool for learning Java programming so they can learn Java programming concepts more frequently from their smartphones. The primary objective is to investigate the feasibility of the proposed m-learning prototype. The proposed application is expected to offer intuitive coding exercises and case study opportunities. Experimental results demonstrate that the overall functionality of the proposed application is feasible for future implementation, with a usability score of 84.